STRATEGI MANAJEMEN PENGELOLAAN KELAS PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MAS AL-WASHLIYAH KISARAN - Siahaan, Adlila Anggriani; Ramadhan, Devina; Wasirin, Nadhilah Uzma (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2023)
In the learning process carried out in the classroom as a teacher, he must have an appropriate and effective and efficient classroom management strategy so that the learning process carried out can run as expected. Given that at this time students carry cellphones at school and they are more focused on their own cellphones. This is where appropriate classroom management strategies are needed, so that students can follow the learning process well. The research method used in this research is qualitative with a descriptive approach. By using interview data collection techniques, observation and documentation. While the informant in this study was one of the teachers at MAS Alwashliyah Kisaran. The results of this study indicate that the teacher has tried to have a good classroom management strategy, but what happens is that not all students can accept the teacher's strategy because students have their own learning types that are different from one another. However, the teacher at MAS Alwashliyah is still trying to change the method or strategy so that all students can accept it well. Key Words: Strategy, Management, Class Management